Analysis of Boundary Conditions for the Simulation of Welding at the Repair of Gas Pipelines with Steel Sleeve - Konar, Radoslav; Mician, Milos; Hopko, Anton (Communications - Scientific letters of the University of Zilina, 2011)
Theoretical part of the manuscript deals with basic information about repair of gas pipeline with steel repair sleeves and simulation programme SYSWELD. Experimental part includes analysis of boundary conditions in two-pass fillet welding joint. Results of the analysis will be used for simulation in simulation programme SYSWELD.